REFORMULATING FOOD SECURITY DEVELOPMENT IN INDONESIA WITH SYSTEMS THINKING AND SERVICE SCIENCE - Hasyimi, Valid
Indonesia has made progress in developing food security. However, several long- term challenges persist. Indonesia struggles to achieve food security due to several factors, such as slow growth in food production, high food loss and waste, price inflation, limited access to nutritious food due to poverty and high prices, and concerns about farmer welfare and sustainability. The complexity of food security has grown due to multifaceted interconnections among various actors and factors, making it categorized as a wicked problem, meaning a problem that is unstructured, difficult to define, multi-perspective, dynamic, and continuously evolving.